STUDI TERHADAP PEMBAGIAN DIVIDEN DAN DAMPAKNYA TERHADAP HARGA SAHAM PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Lestari, Retno Martanti Endah; Permatasari, Putri (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
The purpose of this study was to elucidate whether there is a role in influencing patterns of distribution of dividend stock prices. Data processing methods used were descriptive and comparative analysis. The results of this study indicate that not all issuers listed on the Stock Exchange dividends and the distribution of the dividend were varied. Of the 285 listed companies there are 13 issuers that pay dividends above Rp500 per share and most large issuers that pay dividends (MLBI). Issuers who regularly distribute dividends from 2011-2014 as many as 122 listed companies, with issuers who have an average dividend yield and the standard deviation is SQBB largest and the smallest is the SMMA. Of the 122 listed companies that distribute dividends on a regular basis, issuers that have a relative risk (covariance) is lowest that ASDM. After compared with stock prices, issuers that have a positive correlation between the distribution of dividends and stock prices is larger, ie 75.41%. From this study we can conclude that the theory says that the dividend distribution will affect the stock price can not be generalized. The dividend distribution does not necessarily affect the movement of the stock price still due to the dividend distribution of listed companies is negatively correlated with stock prices. In investing stock investors need not sticking to the distribution of dividends, since not all issuers that pay dividends positively correlated to the stock price.Â Keywords: dividend, stock price, listed on the Stock Exchange